Consequences of prioritisation within long-term care in Denmark, England and Norway: towards increasing inequalities and poorer quality of care?. (1st May 2021) - Ervik, Rune; Lindén, Tord Skogedal
Abstract : Prioritisation concerns choosing something before something else, and in a welfare state context, this is about decisions on distribution, redistribution and rationing. This article investigates consequences of prioritisation within long-term care in Denmark, England and Norway. Analysing interviews with policy actors and policy documents, we find that prioritising home care, combined with increasing targeting of help and restricting institutionalised care towards those with the most severe needs, may reduce both service quality and equality for those not being prioritised. Moreover, monitoring and central control of service provision restrict individual discretion of care workers, with implications for service quality.